STRATEGI KOMISI PEMILIHAN UMUM KOTA BINJAI DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILU SERENTAK TAHUN 2024 - Lisa Theresia; Faisal Andri Mahrawa (Nirta Learning Centre, 2026)
This study aims to analyze the strategies of the General Election Commission (KPU) of Binjai City in increasing voter participation during the 2024 Simultaneous General Election. The background of this research is based on the declining voter turnout in Binjai City, from 82.5% in 2019 to 77.75% in 2024. This phenomenon indicates significant challenges in the election process, particularly in reaching young voters and politically apathetic communities. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews and documentation. The research informants include KPU Binjai commissioners, socialization division staff, as well as several voters from vulnerable and first-time voter groups. The findings show that the KPU of Binjai City has implemented several strategies, such as the Goes to School program, Goes to Campus, Democratic Movie Night, and the use of social media. However, the implementation of these strategies has not been fully effective due to obstacles such as limited funding, low political literacy, and public apathy. This study concludes that the KPU of Binjai City needs to develop more innovative and community-based strategies to increase voter participation, especially among young people and vulnerable groups, in order to support the realization of inclusive and participatory democracy..